Determination of water absorbed dose in a carbon ion beam using thimble ionization chambers - Hartmann, Günther H.; Jäkel, Oliver; Heeg, Peter; Karger, Christian; Krießbach, Alexander (Physics in medicine and biology, 1999)
The method to measure absorbed dose to water in a field of carbon ions as applied for the heavy ion therapy project at the Heavy Ion Research Laboratory in Darmstadt (GSI), Germany, is described in detail. Thimble ionization chambers with a water absorbed calibration factor are applied. The dose obtained with this method was compared with that obtained at the heavy ion therapy facility HIMAC at the National Institute of Radiological Sciences in Chiba, Japan, using the Japanese code of practice. The agreement found was better than 1%. The combined uncertainty of the determination of absorbed dose to water was estimated to amount to 5%.